2023
DOI: 10.1002/adhm.202300367
|View full text |Cite
|
Sign up to set email alerts
|

RNA‐Cleaving DNAzyme‐Based Amplification Strategies for Biosensing and Therapy

Abstract: Since their first discovery in 1994, DNAzymes have been extensively applied in biosensing and therapy that act as recognition elements and signal generators with the outstanding properties of good stability, simple synthesis, and high sensitivity. One subset, RNA‐cleaving DNAzymes, is widely employed for diverse applications, including as reporters capable of transmitting detectable signals. In this review, the recent advances of RNA‐cleaving DNAzyme‐based amplification strategies in scaled‐up biosensing are f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 182 publications
0
14
0
Order By: Relevance
“…14,15 Currently, numerous Dzs are being developed through the SELEX strategy, such as Dzs for RNA sequence-specific cutting and RNA-cutting Dzs for detection of breast cancer cells. With the accomplishments of the SELEX strategy based on the enormous potential of Dzs in molecular sensing detection, 7,15,16 cell imaging, 8,14,17 cancer treatment [18][19][20] and more, Dzs will likely find applications in more fields.…”
Section: Xiaoguang Zhumentioning
confidence: 99%
“…14,15 Currently, numerous Dzs are being developed through the SELEX strategy, such as Dzs for RNA sequence-specific cutting and RNA-cutting Dzs for detection of breast cancer cells. With the accomplishments of the SELEX strategy based on the enormous potential of Dzs in molecular sensing detection, 7,15,16 cell imaging, 8,14,17 cancer treatment [18][19][20] and more, Dzs will likely find applications in more fields.…”
Section: Xiaoguang Zhumentioning
confidence: 99%
“…5,6 However, compared to DNA gene therapeutic agents, RNA is less stable and exhibits lower enzymatic degradation resistance. 7 Finding stable DNA gene therapeutic agents with the same function as siRNA is thus critical to resolving the above issues. 8 DNAzymes with RNA cleavage ability have garnered a great deal of attention in recent years.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Studies have shown that B-cell lymphoma 2 (Bcl-2) and Survivin (Svv) mRNAs are overexpressed in RB cells, suggesting that these two mRNAs might be promising therapeutic targets. , In particular, the eye offers certain anatomical advantages as a target tissue, which is conducive to the development of multifunctional diagnostic nanocontrast agents combining anti-RB gene therapeutic agents with multimodal imaging technology. Currently, the agents mainly used for RB gene therapy are small interfering RNA (siRNA). , However, compared to DNA gene therapeutic agents, RNA is less stable and exhibits lower enzymatic degradation resistance . Finding stable DNA gene therapeutic agents with the same function as siRNA is thus critical to resolving the above issues .…”
Section: Introductionmentioning
confidence: 99%
“…In the era of precision cancer therapy, precise initiation and efficient treatment are crucial issues to ensure satisfactory efficacy, which remains challenging in biomedicine. , Gene therapy, which can modulate disease-related proteins to continuously inhibit tumor proliferation and metastasis at the root, is considered the ultimate panacea for cancer treatment. , Among various gene drugs such as antisense oligonucleotides (ASOs), small interfering RNA (siRNA), , and clustered regularly interspersed short palindromic repeats (CRISPRs), , etc. , DNAzyme has received special attention owing to its flexible design and enzyme-like activity, which enables it to specifically recognize and continuously cleave target genes. However, the current DNAzyme-based gene therapy faces several limitations: (a) low transfection efficiency and insufficient cofactor supply, , (b) poor specificity causing adverse reactions, , and (c) inadequate effects of monotherapy. …”
mentioning
confidence: 99%